2020
DOI: 10.1161/circresaha.119.315185
|View full text |Cite|
|
Sign up to set email alerts
|

Rapamycin-Loaded Biomimetic Nanoparticles Reverse Vascular Inflammation

Abstract: Rationale: Through localized delivery of rapamycin via a biomimetic drug delivery system, it is possible to reduce vascular inflammation and thus the progression of vascular disease. Objective: Use biomimetic nanoparticles to deliver rapamycin to the vessel wall to reduce inflammation in an in vivo model of atherosclerosis after a short dosing schedule. Methods and Results: Biomimetic nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 28 publications
2
94
0
Order By: Relevance
“…While oral atorvastatin inhibits macrophage proliferation indirectly via systemic cholesterol and ApoB-lipoprotein reductions, direct targeting of macrophage proliferation may emerge as a potent add-on therapy to support plaque regression. Anti-proliferative drugs such as paclitaxel and methotrexate or mTOR-inhibitor rapamycin, incorporated into a lipid nanoparticle LDE resembling low-density lipoproteins or biomimetic nanoparticles, induced plaque regression and loss of plaque macrophages in murine and rabbit models of atherosclerosis with limited systemic toxicity [4,7,11]. More recently, LDE-paclitaxel was injected into eight patients with aortic atherosclerosis six times every 3 weeks, and computer tomography images of the atherosclerotic aortas were compared before and after 1-2 months of treatment with those obtained in untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…While oral atorvastatin inhibits macrophage proliferation indirectly via systemic cholesterol and ApoB-lipoprotein reductions, direct targeting of macrophage proliferation may emerge as a potent add-on therapy to support plaque regression. Anti-proliferative drugs such as paclitaxel and methotrexate or mTOR-inhibitor rapamycin, incorporated into a lipid nanoparticle LDE resembling low-density lipoproteins or biomimetic nanoparticles, induced plaque regression and loss of plaque macrophages in murine and rabbit models of atherosclerosis with limited systemic toxicity [4,7,11]. More recently, LDE-paclitaxel was injected into eight patients with aortic atherosclerosis six times every 3 weeks, and computer tomography images of the atherosclerotic aortas were compared before and after 1-2 months of treatment with those obtained in untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, biomimetic nanoparticles were synthesized using membrane proteins purified from activated J774 macrophages and loaded with rapamycine. In a model of ApoE-/-mice with atherosclerotic plaques, it was observed that systemic injection of these hybrid NPs was able to suppress cell proliferation within the aorta [104].…”
Section: Biomimetic Nanoparticlesmentioning
confidence: 99%
“…In a lipopolysaccharide (LPS) induced murine model of sepsis, administration of biomimetic nanoparticles derived from macrophages decreased pro-inflammatory genes (IL-6, IL-1b, and TNF-α), and increased anti-inflammatory genes (IL-10 and TGF-β) (Molinaro et al, 2019). The intrinsic anti-inflammatory effects of these biomimetic leukosomes have been demonstrated in other disease models including inflammatory bowel disease (IBD) (Corbo et al, 2017), atherosclerosis (Martinez et al, 2018;Boada et al, 2020), and cancer (Martinez et al, 2018). Most recently, we have shown the capability of leukosomes to home to sites of vascular inflammation in the apo E deficient hypercholesterolemic mouse.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…In this model, the elevated levels of cholesterol cause the accumulation of lipid and macrophages in the aorta. Leukosomes were more efficient than standard LNPs at delivering rapamycin to the aorta, where the rapamycin inhibited macrophage proliferation and generation of inflammatory cytokines (Boada et al, 2020). While significant work remains to be done testing the efficacy of this platform in larger animal models, there is great promise for biomimetic nanoparticles to create new mRNA therapeutics that has the potential to selectively target all the inflammatory-based conditions.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%